Effect of DHA and two plant extracts on the production of fattening pigs infected with PRRS - Angeles-Marin, Alvaro Alberto; Loeza-Limon, Ruben; Vicente-Martínez, Jorge Genaro; Villagomez-Cortes, Jose Alfredo; Mariscal-Landin , Gerardo; Vega-Murillo, Vicente Eliezer (Ecosistemas y Recursos Agropecuarios, 2024)
Pig Respiratory and Reproductive Syndrome (PRRS) is a disease with economic repercussions for pig farmers worldwide as it causes low feed efficiency and, therefore, less weight gain in the fattening stage. The effect of dietary supplementation with docosahexaenoic acid (DHA), turmeric oleoresin and capsicum (EP, plant extracts) on the productive performance of fattening pigs and on the health of a herd affected by PRRS was evaluated. Nine-hundred and sixty fattening pigs with an initial average weight of 5.21 ± 0.065 kg was randomly assigned to one of four treatments, T1, control; T2, DHA; T3, EP; T4, DHA+EP. The variables analyzed were weight at day 70 of life (P70), weight at market (PM), daily weight gain at day 70 of life (GDP70), daily weight gain to market (GDPM), feed conversion at day 70 of life (CA70) and feed conversion at market (CAM). T2 and T4 diets exceeded the control and T3 in P70 and GDP (P < 0.05), T2 and T4 did better than the control and T3 in CA70 (P < 0.05). T2, T3, and T4 surpasssed the control in PM (P < 0.05). All pigs had antibodies against PRRS throughout the study, although pigs in the second fattening cycle showed higher IgG values for T2 and T4. The cost of production for T2, T3 and T4 was lower for GDPM, CAM and PM. In conclusion, the treatments T2, T3, and T4 were superior to the control in PM and therefore, the use of DHA and phylogens wasp cost-effective.
Keywords: Pigs; docosahexaenoic acid; turmeric and capsicum oleoresin; virus